Leadership and the relation between school culture and identity - Reda, Samiha (2015)
The main purpose of this dissertation is to examine the role of leadership when building a school’s identity and culture and to examine the relation between identity and culture. The research explores the different definitions of both identity and culture, and how it is seen in the school. Moreover, the research explores the concept of inclusion of students with special educational needs. An ethnographic case study was conducted in a Catholic primary school in the UK. The research methods that were employed were observations, semi-structured interview, informal interviews and a documentary analysis. The research takes into consideration different perspectives of school members, since identity and culture can be seen through their actions. The findings show a relation between identity and culture, since the identity of the school influences it’s culture and provides an explanation to the decisions taken in the school. Also, the results suggest that the leader’s values are what mainly shapes a school’s culture and identity. Key words: “identity”, “culture”, “leadership”, “case study”, “inclusion”, “ethnography” and “values”.